INCLUSIVE EDUCATION IN TIMES OF DIVERSITY: PUBLIC POLICIES AND TRANSFORMATIVE PRACTICES (Editora Impacto Científico, 2025)
Inclusive education, in contexts of growing diversity, requires strategies that align robust public policies with transformative pedagogical practices. Ensuring enrollment is necessary but insufficient; the goal is to secure full participation and meaningful learning for all students, regardless of socioeconomic background, culture, gender or disability. Although legal and regulatory advances demonstrate institutional commitment, gaps in implementation persist and reproduce regional and institutional inequalities. Transformative practices include active methodologies, Universal Design for Learning principles, and critical use of assistive technologies, integrated into pedagogy that recognizes difference as an educational resource. Effective inclusive schools develop collaborative processes that involve leadership, teachers, families and students in decision-making, ongoing assessment and curricular adaptation. Evidence and case studies indicate that well-articulated policies reduce barriers and promote equity, but their impact depends on adequate funding, continuous teacher education and technical support. Initial and continuing teacher education is central: educators trained in inclusive practices and in the management of pedagogical and technological resources are essential to operationalize policy. Furthermore, intersectoral coordination among education, health and social services enhances the capacity to address students’ complex needs. Ultimately, affirming inclusive education in times of diversity means recognizing schools as political spaces for social transformation, requiring collective commitment, participatory evaluation and sustainable policies. It is essential to implement ongoing monitoring, action-research and stable financing to ensure contextualized effectiveness and institutional strengthening. Accountability mechanisms and community engagement enable policies to translate into classroom practice and foster iterative improvement. These measures support scaling and adaptation across diverse local contexts and sustainability.DOI: https://doi.org/10.56238/edimpacto2025.092-003